"Freezing", morphing, and folding of stretchy tough hydrogels. Issue 29 (12th July 2017) - Li, Tianzhen; Wang, Jiahui; Zhang, Liyun; Yang, Jinbin; Yang, Mengyan; Zhu, Deyong; Zhou, Xiaohu; Handschuh-Wang, Stephan; Liu, Yizhen; Zhou, Xuechang
Abstract : Complex 3D structures were designed and fabricated from tough hydrogels by simply soaking Fe 3+ ions or patterning. Abstract : Highly stretchable and tough Ca-alginate/polyacrylamide hydrogels were "frozen" and folded into program-controlled shapes by exposing them to an Fe 3+ ion aqueous solution. The elastic modulus of the as-made tough gels increased either in bulk or locally up to 2.90 MPa, while the toughness remained within the range from 8.18 to 4.41 kJ m −2 .